ENHANCING THE COMPETITIVE ADVANTAGE OF MSME’S VIA DIGITAL MARKETING AND THE "SEGITIGA EMAS" TOURISM PROGRAM: A CASE STUDY FROM MUMBULSARI, INDONESIA - Indah Ibanah; Julita Hasanah; Meidiana Purnamasari; Agus Supriono; Evita Soliha Hani (Jurnal Abdimas Terapan, 2024)
Mumbulsari Village of Jember, has economic development potential through Micro, Small, and Medium Enterprises (MSMEs). However, the local MSMEs face several challenges, such as limited capital, the development of quality and competitive products, and the lack of market information, which have become major obstacles to the village's economic growth, especially during the pandemic. This community service program aims to provide assistance to MSMEs in Mumbulsari through marketing training programs and the development of highly competitive products. The method used is a tiered Focus Group Discussion, at the sub-district, village, and MSME levels. The assistance program includes education on the importance of branding and technical training on using the Whatsapp Business platform and independently producing product photos by utilizing available resources. In addition, this initiative is integrated with the "Segitiga Emas" tourism program, in which Mumbulsari is positioned as a downstream tourism village. It is hoped that through this collaboration, local MSMEs can improve their production capacity, expand market access, and increase product competitiveness in wider markets. The results of this activity are expected to strengthen the local economy and position Mumbulsari Village as one of the leading destinations in the sustainable tourism ecosystem in Jember.